Surfaceome and Exoproteome Dynamics in Dual-Species Pseudomonas aeruginosa and Staphylococcus aureus Biofilms - Reigada, Inés; San-Martin-Galindo, Paola; Gilbert-Girard, Shella; Chiaro, Jacopo; Cerullo, Vincenzo; Savijoki, Kirsi; Nyman, Tuula A.; Fallarero, Adyary; Miettinen, Ilkka (Frontiers in Microbiology, 2021)
Bacterial biofilms are an important underlying cause for chronic infections. By switching into the biofilm state, bacteria can evade host defenses and withstand antibiotic chemotherapy. Despite the fact that biofilms at clinical and environmental settings are mostly composed of multiple microbial species, biofilm research has largely been focused on single-species biofilms. In this study, we investigated the interaction between two clinically relevant bacterial pathogens (Staphylococcus aureus and Pseudomonas aeruginosa), by label-free quantitative proteomics focusing on proteins associated with the bacterial cell surfaces (surfaceome), and proteins exported/released to the extracellular space (exoproteome). The changes observed in the surfaceome and exoproteome of P. aeruginosa pointed towards higher motility and lower pigment production when co-cultured with S. aureus. In S. aureus, lower abundances of proteins related to cell wall biosynthesis and cell division, suggesting increased persistence, were observed in the dual-species biofilm. Complementary phenotypic analyses confirmed the higher motility and the lower pigment production in P. aeruginosa when co-cultured with S. aureus. Higher antimicrobial tolerance associated with the co-culture setting was additionally observed in both species. To the best of our knowledge, this study is among the first systematic explorations providing insights into the dynamics of both the surfaceome and exoproteome of S. aureus and P. aeruginosa dual-species biofilms.